EFFECTS OF CARRAGEENAN COATING ON ORGANOLEPTIC QUALITY OF BOILED SHRIMP DURING REFRIGERATION STORAGE - Nurlaila Ervina Herliany; Joko Santoso; Ella Salamah (Jurnal Agroindustri, 2013)
One of the most popular seafood in the world is shrimp, including cooked shrimp. Boiled shrimp is a value added product with high protein content, specific taste, ready to eat, and have an interested colour for consumers. Boiled shrimp must be protected from quality deterioration during storage. The research was carried out to study the effect of carrageenan coating to inhibit the quality deterioration of boiled shrimp based on organoleptic evaluation during refrigeration storage (4-6oC). Peeled undevined (PUD) vannamei (Litopenaeus vannamei) with size 60-70 was used as object. The boiled shrimps treated with two treatmens, which were coated and uncoated boiled shrimps. Application of coating carrageenan on boiled shrimp indicate that coating application could extend its shelf life, proved by higher organoeptic value than uncoated product, based on organoleptic evaluation for frozen boiling shrimp (SNI 01-2346-2006).